Conventional protein kinase C isoforms differentially regulate ADP- and thrombin-evoked Ca2+ signalling in human platelets. Issue 6 (December 2015) - Lever, Robert A.; Hussain, Azhar; Sun, Benjamin B.; Sage, Stewart O.; Harper, Alan G.S.
Graphical abstract: Highlights: The effects of PKC inhibitors on ADP- and thrombin-evoked Ca 2+ fluxes were observed. Conventional PKC isoforms modulate platelet Ca 2+ signalling in an agonist-dependent manner. PKC works to accelerate the activity of SERCA in response to both agonists. Thrombin-evoked Ca 2+ signals are also modulated via an effect on the Na + /K + -ATPase. Abstract: Rises in cytosolic Ca 2+ concentration ([Ca 2+ ]cyt ) are central in platelet activation, yet many aspects of the underlying mechanisms are poorly understood. Most studies examine how experimental manipulations affect agonist-evoked rises in [Ca 2+ ]cyt, but these only monitor the net effect of manipulations on the processes controlling [Ca 2+ ]cyt (Ca 2+ buffering, sequestration, release, entry and removal), and cannot resolve the source of the Ca 2+ or the transporters or channels affected. To investigate the effects of protein kinase C (PKC) on platelet Ca 2+ signalling, we here monitor Ca 2+ flux around the platelet by measuring net Ca 2+ fluxes to or from the extracellular space and the intracellular Ca 2+ stores, which act as the major sources and sinks for Ca 2+ influx into and efflux from the cytosol, as well as monitoring the cytosolic Na + concentration ([Na + ]cyt ), which influences platelet Ca 2+ fluxes via Na + /Ca 2+ exchange. The intracellular store Ca 2+ concentration ([Ca 2+ ]st ) was monitored using Fluo-5N, the extracellular Ca 2+ concentration ([Ca 2+ ]ext ) was monitored using Fluo-4 whilst [Ca 2+ ]cyt and [Na + ]cyt were monitored using Fura-2 and SFBI, respectively. PKC inhibition using Ro-31-8220 or bisindolylmaleimide I potentiated ADP- and thrombin-evoked rises in [Ca 2+ ]cyt in the absence of extracellular Ca 2+ . PKC inhibition potentiated ADP-evoked but reduced thrombin-evoked intracellular Ca 2+ release and Ca 2+ removal into the extracellular medium. SERCA inhibition using thapsigargin and 2, 5-di(tert-butyl) l, 4-benzohydroquinone abolished the effect of PKC inhibitors on ADP-evoked changes in [Ca 2+ ]cyt but only reduced the effect on thrombin-evoked responses. Thrombin evokes substantial rises in [Na + ]cyt which would be expected to reduce Ca 2+ removal via the Na + /Ca 2+ exchanger (NCX). Thrombin-evoked rises in [Na + ]cyt were potentiated by PKC inhibition, an effect which was not due to altered changes in non-selective cation permeability of the plasma membrane as assessed by Mn 2+ quench of Fura-2 fluorescence. PKC inhibition was without effect on thrombin-evoked rises in [Ca 2+ ]cyt following SERCA inhibition and either removal of extracellular Na + or inhibition of Na + /K + -ATPase activity by removal of extracellular K + or treatment with digoxin. These data suggest that PKC limits ADP-evoked rises in [Ca 2+ ]cyt by acceleration of SERCA activity, whilst rises in [Ca 2+ ]cyt evoked by the stronger platelet activator thrombin are limited by PKC through acceleration of both SERCA and Na + /K + -ATPase activity, with the latter limiting the effect of thrombin on rises in [Na + ]cyt and so forward mode NCX activity. The use of selective PKC inhibitors indicated that conventional and not novel PKC isoforms are responsible for the inhibition of agonist-evoked Ca 2+ signalling.